2023
DOI: 10.3324/haematol.2023.283288
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signatures of cardiorenal dysfunction in plasma from sickle cell patients as a function of therapeutic transfusion and hydroxyurea treatment

Abstract: Metabolomics studies in sickle cell disease (SCD) have been so far limited to tens of samples, owing to technical and experimental limitations. To overcome these limitations, we performed plasma metabolomics analyses on 596 samples from patients with sickle cell sickle cell disease (SCD) enrolled in the WALK-PHaSST study. Clinical covariates informed the biological interpretation of metabolomics data, including genotypes (hemoglobin SS, hemoglobin SC), history of recent transfusion (HbA%), response to hydroxyu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
3
7
0
Order By: Relevance
“…While mitapivat was initially designed to treat hemolytic anemia in patients with PK deficiency, we showed that patients with SCD also have reduced PK enzyme activity and stability, which is consistent with the literature 5 . Previous metabolomics studies describe slightly increased levels of glycolytic intermediates upstream of PK in RBCs from patients with SCD 4,25,26 . Taken together, these findings provide a rationale for the treatment of SCD with mitapivat.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…While mitapivat was initially designed to treat hemolytic anemia in patients with PK deficiency, we showed that patients with SCD also have reduced PK enzyme activity and stability, which is consistent with the literature 5 . Previous metabolomics studies describe slightly increased levels of glycolytic intermediates upstream of PK in RBCs from patients with SCD 4,25,26 . Taken together, these findings provide a rationale for the treatment of SCD with mitapivat.…”
Section: Discussionsupporting
confidence: 85%
“… 5 Previous metabolomics studies describe slightly increased levels of glycolytic intermediates upstream of PK in RBCs from patients with SCD. 4 , 25 , 26 Taken together, these findings provide a rationale for the treatment of SCD with mitapivat. We did not observe significant differences between patients and HCs in glycolytic and PPP intermediates, except for glyceraldehyde‐3‐phosphate, 6‐phosphate gluconolactone, and pentose phosphate (and/or metabolites with the same respective mass to charge ratio, legend Figure 4 ).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…267 The mechanisms involved in the sodium-glucose cotransporter-2 inhibitor-triggered delay in the progression of chronic heart failure seem to be mediated by a reduction in oxidative and ER stress, restoration of mitochondrial function, and a decrease in proinflammatory and profibrotic pathways. 267 Therefore, new mechanisms using the multiomics approach, such as genomics, metabolomics, and transcriptomics, 268–270 should be involved in mapping the pathogenesis of cardiorenal crosstalk to advance new therapeutic strategies in this field. Moreover, to maximize the potential key crosstalks within the renocardial axis, which could lead to a single-target treatment of multiple pathologies, revolutionary tools such as the computational ecosystems for multiorgan diseases 271 might be integrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that S1P can cooperatively bind to deoxyhemoglobin upon its complexing with DPG, further stabilizing the tense deoxygenated state. While beneficial for acclimatization to hypoxia, this mechanism is actually deleterious in the context of sickle cell disease [52], as it promotes sickle hemoglobin crystallization, driving cardiorenal dysfunction [53,54]. Among other lipid classes, phosphatidylserines participate in RBC removal from the bloodstream upon loss of phospholipid asymmetry, a process that is maintained by ATP-dependent flippases like ATP11C (EC 7.6.2.1) [55,56].…”
Section: Red Blood Cell Metabolismmentioning
confidence: 99%